Stylistic In Maya Angelou Selected Poems - Ismah, Nurul; Maca, Sudirman; Abeng, Andi Tenri (Fakultas Sastra, Universitas Bosowa, 2024)
This study aims to find out the language features and their meaning of Maya Angelou’s selected poems. The study used qualitative descriptive approach by applying the theory of Geoffrey Leech’s in analyzing the level of language. The results show that there were four language levels found in Maya Angelou’s selected poems. The first was phonological level, which divided into alliteration, assonance, consonance, and rhyme scheme. The second was grammatical level which are simple present tense, simple present perfect tense and simple past tense to see the relation between tenses and the meaning of the poem. The third was Lexical level such as nouns, verbs, adjectives and pronouns. The semantically level consisted of figurative language were simile, hyperbole, metaphor, and imagery. For the Phenomenal Woman poem had a message for all women to convey that radiate your own beauty, without see the other woman beauty but self-confident. Our Grandmothers poem reveal that the woman avoided slaved and tell her children the worst that could happen, it was feeling injustice. Mother, a Cradle to Hold Me poem conveyed the mother love and speaker love to his mother and his afraid to lose his mother